2016
DOI: 10.1177/0961203316651738
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits type I interferon-induced production of macrophage migration inhibitory factor in patients with systemic lupus erythematosus

Abstract: Objective Macrophage migration inhibitory factor (MIF) is a key regulator of both atherosclerosis and systemic lupus erythematosus (SLE), yet factors leading to its overproduction remain unclear. To explore regulation of MIF in SLE, we studied effects and potential mechanisms of type I interferon (IFN) and artesunate (ART), an anti-malarial agent extracted from Chinese herbs, on levels of MIF. Methods Serum and peripheral blood cells from SLE patients and healthy controls were measured for MIF levels by ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Arch Med Sci the major defect is a loss of self-tolerance, which results in the production of autoreactive lymphocytes [38]. In this study, we found that there was a significant association between MIF levels and SLEDAI scores (of both < 8 and ≥ 8) of SLE patients, and this finding is similar to Diaz Rizo et al [39] and Feng et al [28]. Our findings further revealed that disease duration in SLE patients for both year < 5 and year ≥ 5 had significantly higher plasma/ serum MIF levels, compared to healthy controls patients in a matched population.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Arch Med Sci the major defect is a loss of self-tolerance, which results in the production of autoreactive lymphocytes [38]. In this study, we found that there was a significant association between MIF levels and SLEDAI scores (of both < 8 and ≥ 8) of SLE patients, and this finding is similar to Diaz Rizo et al [39] and Feng et al [28]. Our findings further revealed that disease duration in SLE patients for both year < 5 and year ≥ 5 had significantly higher plasma/ serum MIF levels, compared to healthy controls patients in a matched population.…”
supporting
confidence: 85%
“…The articles were subjected to screening, and 31 duplicate articles as well as 202 articles with reviewed titles and abstract were excluded. Twenty-two articles were retrieved for further detailed assessments, and 9 articles were further excluded (3 have no full texts, 3 have no available data, and 3 were only review papers), leaving 13 articles meeting the inclusion criteria [16][17][18][19][20][28][29][30][31][32][33] (Figure 1). Among the 13 included articles, 5, 3, 1, and 1 were from PubMed [16,18,20,28,29,32], Embase [17,30,31], Web of Science [19], and several Chinese databases [33], respectively.…”
Section: Literature Searchmentioning
confidence: 99%
“…MIF has been reported to play a role in SLE pathogenesis,3 as it is associated with disease activity, organ damage and glucocorticoid use 3, 17, 18. Our analysis revealed that serum MIF was 3.5 times higher in SSc patients than in SLE patients.…”
Section: Discussionmentioning
confidence: 57%
“…MIF has been reported to play a role in SLE pathogenesis, 3 as it is associated with disease activity, organ damage and glucocorticoid use. 3,17,18 Our analysis revealed that serum MIF was 3.5 times higher in SSc patients than in SLE patients. This may suggest that while MIF not only can play a pathogenic role in inflammatory autoimmune diseases, such as SLE, but may also play a part in diseases that have a prominent fibrotic phase, such as that seen in SSc.…”
Section: Discussionmentioning
confidence: 67%
“…Numerous studies have revealed that the immunoregulatory cytokine MIF participates in the pathogenesis of SLE with respect to both disease initiation and progression [7]. MIF expression is increased in SLE patients and positively correlates with disease activity [8]. MIF is overexpressed in lupus-prone mice and renal injury is alleviated in Mif −/− MRL/lpr mice [9].…”
Section: Introductionmentioning
confidence: 99%